ANALISIS DAN RANCANGAN SISTEM INFORMASI MONITORING PIUTANG PELANGGAN BISNIS MENGGUNAKAN WHATSAPP GATEWAY API - Armiati, Sari; Mulyati, Khairaningrum; Wiranda, Adi Tiya (Universitas Logistik dan Bisnis Internasional, 2024)
PT XYZ as a company engaged in the service sector has services for sending letters and packages on credit to partners who already have cooperation agreements. Every incoming shipment from partners will become receivable, then the company records each incoming receivable so that it is monitored so that partners do not pay receivables beyond the due date. Activities that support the management of receivables are reporting of each receivable to determine the amount and maturity of the receivable. The current accounts receivable management business process is still semi-computed, therefore it is necessary to have a special system that can manage accounts receivable activities properly so that they can be controlled from period to period by providing receivable notification features to partners. In this study, which is part of the development of a receivables information system, which is reflected in the financial rules regarding receivables. Research activities are carried out in the analysis phase and the information system design phase. Information system analysis uses Porter's value chain to describe ongoing activities and BPMN notation to model the main activity business processes. As for the design is done using an object-oriented approach. In designing this system, the tools used to describe processes and databases are designed using the Unified Modeling Language (UML) which provides accounts receivable management features, notifications using Whatsapp chat media and accounts receivable reporting features. The output of the research is in the form of a report on the design of an information system for monitoring receivables using the Whatsapp Gateway API, software documents and research publications. The design of the information system built can make it easier for system developers to build management systems and monitor receivables at PT XYZ.